A Critical Discourse Analysis of Obesity in Bangladeshi Newspapers - Karim, SM Samuel Karim (Journal of Natural Language and Linguistics, 2024)
This paper investigates the obesity discourse in Bangladeshi newspapers. The paper uses Critical Discourse Analysis (CDA) to examine how the Bangladeshi media frames obesity and how this framing influences public perceptions of the issue. The analysis reveals that obesity is framed in a negative light, with a focus on individual responsibility and blame. The composition strengthens the idea that obesity is an individual problem. instead of a public health crisis. Content analysis was used to assess the types and frequency of obesity-related news items on causes, determinants, impacts, and solutions. The qualitative research design was used to explore the framing of obesity through discourse analysis. The study uncovered that obesity was underrepresented in both newspapers. Individual causes and solutions were the most prominent news items in both newspapers, whereas genetic and biological determinants were less likely to be presented. The data for this study came from two major Bangladeshi newspapers: The Daily Star and The Daily Observer. The adult population, around 18 and older, that is capable of taking responsibility, was the target audience. A total of 80 articles were gathered to collect data, 40 from each newspaper, from the years 2016 to 2024. This method was chosen because it allowed for a closer look at the underlying ideology and power structures that affect obesity discourse in Bangladeshi media. Discourse analysis found three major frames—legitimization, responsibility, and stereotype—that meant to indicate individual responsibility and (by implication) social responsibility. In each newspaper, stereotypes, weight stigma, and shrill discourse were mentioned. Framing analysis found that news stories about obesity tended to transfer medical costs onto individuals rather than emphasizing the responsibility of the food and beverage industry. The use of stereotype frames was more prevalent in both newspapers. The presence of stereotype frames was greater in both newspapers. Specifically, older people are at higher risk of obesity. Children and teenagers who are addicted to electronic devices are more likely to develop obesity. Finally, the paper concludes by arguing that in order to reduce stigma and promote public health, one must take into account the complex social and economic factors that contribute to the problem.